Membangun Kepribadian Religus Anak Lewat Pengelolaan Program Keagamaan di Raudhatul Athfal Faturrahman - Mesran Mesran; Wartomo Wartomo; Martono Martono (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This study aims to analyze the implementation, infrastructure, and evaluation of religious program management at Raudhatul Athfal (RA) Faturrahman, focusing on its role in shaping the religious personality of early childhood. Employing a qualitative approach through a case study methodology, the research was conducted at RA Faturrahman in North Sumatra, involving the Principal, teachers, and parents as key subjects. Data were collected using participant observation, semi-structured interviews, and documentation, and subsequently analyzed using the Miles, Huberman, and Saldana model, with findings verified through triangulation. The study results indicate that the structured and systematic management of religious programs has a positive and significant impact on the formation of children's religious character. This impact is evidenced by improvements in aspects such as worship (independent prayer and shalat), morals (politeness and honesty), social awareness, and religious knowledge. The critical success factors identified are the consistent role modeling by teachers and a strong synergy between the school and families, with dual support enhancing the children's character development. Furthermore, the most effective learning methods are storytelling (especially when enhanced with visual media) and play-based learning. While the availability of adequate infrastructure positively correlates with program optimization, the CIPP evaluation identified several key challenges: low teacher competency (with nearly half still relying on conventional methods), partial parental involvement, and the pervasive negative influence of media. The institution must address these through solutions such as continuous teacher training and intensified communication with parents to sustain and maximize program outcomes. This research concludes that the optimal management of religious programs serves as a crucial long-term investment in cultivating a generation endowed with a strong religious character.